Large Bartholin's gland cyst in a premenarchal girl: a rare clinical finding - Popovic, Nusret; Zvizdic, Zlatan; Milisic, Emir; Jonuzi, Asmir; Karamustafic, Azra (Iranian Journal of Pediatric Surgery, 2018)
Disorders related to Bartholin’s duct and glands affect approximately 2% of young women, and are very rare in premenarchal girls. Bartholin’s gland cysts are usualy small, do not cause any symptoms and resolve spontaneously. However, symptomatic larger cysts require medical treatment. Although many treatment modalities have been applyed, the best approach has not yet been found. Treatment modalities of Bartholin’s cyst include application of silver nitrate to the abscess cavity, incision and drainage of the cyst, curettage of the abscess cavity, placement of “Word catheter”, marsupialization, needle aspiration and alcohol sclerotheraphy, carbon dioxide laser excision and surgical gland excision. Here, we report a case of a large, soft, regular contoured painless Bartholin’s cyst located in the left labia minora with a diameter of 8 x 5 cm in an 11-year-old premenarchal girl, treated by surgical gland excision after previous unsuccessful incision and aspiration of the cyst.